IMPLEMENTASI SISTEM INFORMASI PENYEWAAN STUDIO MUSIK RENTAL STUDIO 14 - Nuzuliarini Nuris; Pepri Pratama; Priyono Priyono (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
Information system rental studio 14 at the time was still running manually. transactions made still encounter many problems, such as during the booking process, where customers have to come directly to the studio to book a studio room. due to lack of information, the customer does not know at that time the rental schedule is full or has been ordered by another customer. This of course is very detrimental to customers who have come but do not order because the desired booking schedule is already filled or full. The research was conducted using the waterfall approach method which was carried out in succession in the software development process. To solve the existing problem, it will be implemented with a music studio rental system on a web basis at the studio rental14. This application is considered sufficient to provide convenience in the booking process for customers because it has obtained fast and accurate information and makes it easier to record music studio rental transactions so that reports can be made in a short time.